2012
DOI: 10.1016/j.ocemod.2012.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The response of the Ligurian and Tyrrhenian Seas to a summer Mistral event: A coupled atmosphere–ocean approach

Abstract: In this paper the effect of a summer Mistral event on the Ligurian and Tyrrhenian Seas in the northwestern Mediterranean is discussed, using a coupled numerical model and satellite and in situ observations. The focus is on the spatial and temporal distribution of the ocean mixed layer response to the strong winds, and on how this is affected by atmosphere-ocean coupling. The model used is the Coupled Ocean-Atmosphere Mesoscale Prediction System (COAMPS Ò1), developed at the Naval Research Laboratory. This syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 61 publications
3
41
0
Order By: Relevance
“…When taking into account that QuikSCAT shows higher wind speeds than the buoy in the Gulf of Lion, these spatial patterns are robust (tested with a wind speed dependent QuikSCAT bias, not shown). Close to the eastern coast of the Gulf of Lion, intensified cooling has been observed during Mistral events and in coupled simulations (Small et al 2012;Schaeffer et al 2011). Renault et al (2012) studied a Tramontane event in coupled simulations and found a decreasing sea surface temperature in the western part of the Gulf of Lion.…”
Section: Effects Over the Mediterranean Seamentioning
confidence: 95%
“…When taking into account that QuikSCAT shows higher wind speeds than the buoy in the Gulf of Lion, these spatial patterns are robust (tested with a wind speed dependent QuikSCAT bias, not shown). Close to the eastern coast of the Gulf of Lion, intensified cooling has been observed during Mistral events and in coupled simulations (Small et al 2012;Schaeffer et al 2011). Renault et al (2012) studied a Tramontane event in coupled simulations and found a decreasing sea surface temperature in the western part of the Gulf of Lion.…”
Section: Effects Over the Mediterranean Seamentioning
confidence: 95%
“…The atmospheric model within the MORCE system is the non-hydrostatic weather research and forecasting model (WRF) version 3.1.1 of the National Center for Atmospheric Research (NCAR) (Skamarock et al 2008). The domain covers the Mediterranean basin in line with COR-DEX requirements with a horizontal resolution of 20 km.…”
Section: Morce Platformmentioning
confidence: 99%
“…The top of the seasonal thermocline is typically located at depths between 25 and 45 m [ Jurado et al ., ]. In the Tyrrhenian Sea, similar stratification strength can be found [ Small et al ., ], and depths as shallow as 15–30 m are reached as early as May [ D ' Ortenzio et al ., ]. At the other extreme, off the coasts of Florida, the top of the seasonal thermocline occurs deeper, around 100 m in November [ SAIC , ].…”
Section: Seismic Imaging Of Shallow Oceanographic Structuresmentioning
confidence: 99%